IoT-Enabled Cybersecurity for Datacenters - Real-Time Threat Monitoring and Incident Response - Mahesh Kolli, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive analysis of an IoT-enabled cybersecurity implementation at a major data center service provider operating across multiple regions. It examines the integration of advanced artificial intelligence and machine learning models with IoT sensors to enhance threat detection and incident response capabilities. The platform's innovative approach combines real-time infrastructure monitoring with automated response mechanisms, leveraging continuous learning algorithms to adapt to evolving cyber threats. By analyzing patterns in power consumption, cooling systems, and network behavior, the system demonstrates significant improvements in threat detection and response efficiency. The implementation showcases how intelligent IoT integration in data center security can strengthen operational resilience while ensuring regulatory compliance across critical sectors including banking, healthcare, and telecommunications.
Keywords: Infrastructure Security; Artificial Intelligence; IoT Integration; Threat Intelligence; Automated Response